2006
DOI: 10.1074/jbc.c600209200
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of an Arginine Residue into the Transmembrane Segments Corrects Protein Misfolding

Abstract: Deletion of Phe-508 (⌬F508) in cystic fibrosis transmembrane conductance regulator causes cystic fibrosis because of misfolding of the protein. P-glycoprotein (P-gp) containing the equivalent mutation (⌬Y490) is also misfolded but can be rescued with drug substrates. Whether rescue is due to direct binding of drug substrate to the transmembrane (TM) segments or to indirect effects on cellular protein folding pathways is still controversial. P-gpdrug substrate interactions likely involve hydrogen bonds. If the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…3 shows that the 150-kDa immature protein was sensitive to both endoglycosidases, whereas the 170-kDa protein was only sensitive to endoglycosidase F. These results indicate that the 150-kDa immature proteins were only core-glycosylated, whereas the 170-kDa mature proteins were processed in the Golgi. Cell-surface labeling studies showed that only the mature 170-kDa protein was labeled (data not shown) and confirmed the previous observation that the 170-kDa protein was at the cell surface (8,9). Similar results were obtained with the other arginine mutants (data not shown).…”
Section: Effect Of Tm1 Arginines On Maturation Of Processing Mutantsupporting
confidence: 79%
See 1 more Smart Citation
“…3 shows that the 150-kDa immature protein was sensitive to both endoglycosidases, whereas the 170-kDa protein was only sensitive to endoglycosidase F. These results indicate that the 150-kDa immature proteins were only core-glycosylated, whereas the 170-kDa mature proteins were processed in the Golgi. Cell-surface labeling studies showed that only the mature 170-kDa protein was labeled (data not shown) and confirmed the previous observation that the 170-kDa protein was at the cell surface (8,9). Similar results were obtained with the other arginine mutants (data not shown).…”
Section: Effect Of Tm1 Arginines On Maturation Of Processing Mutantsupporting
confidence: 79%
“…Processing mutations appear to inhibit folding by disrupting packing of TM segments at the interface between the TMDs (6), a defect that can be repaired by expression in the presence of drug substrates (6,7). Drug substrates appear to rescue P-gp processing mutants through direct interactions with the TM segments because their effects can be mimicked by introducing arginine mutations into positions predicted to line the drug binding domain such as position 65 in TM segment 1 (8,9). It was found that the L65R mutation promoted maturation of P-gp processing mutants such as ⌬Y490 and G251V (9).…”
mentioning
confidence: 99%
“…Better understanding of how Mdr transporters respond conformationally to dissimilar substrates in a transport-competent manner would add mechanistically important clues to how dissimilar compounds are actively exported by such transporters. For example, in a P-glycoprotein mutant that is defective in biogenesis, it has been reported that mutations in the binding site improve protein maturation and that this effect can also be achieved by substrates (27)(28)(29)(30)(31)(32). Thus, binding site modifications also have substrate-mimicking effects in this ATP-binding cassette Mdr transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes to the TM5-TM6 hairpin can affect distal folding events. Some changes in TM5 (I306A or G) or in TM6 (F343Y) in the ⌬Y490 P-gp mutant also caused the mutant protein to be unstable because cells expressing these mutants contained relatively large amounts of a 130-kDa degradation product (21). An example of the effects of Arg and Tyr changes to Phe 343 in mutant ⌬Y490 P-gp is shown in Fig.…”
Section: Screening Tm3 Single Cysteine Mutants For Activation Of Atpamentioning
confidence: 99%
“…essing mutants by a direct mechanism because suppressor mutations (arginines) introduced into TM segments 5 (I306R) and 6 (F343R) also promoted maturation of the protein (21). One explanation for this observation was that the arginine residues mimicked the effects of drug substrates by promoting interactions among the TM segments.…”
mentioning
confidence: 99%